STUDY OF THE RELATIONSHIP BETWEEN SEMANTIC PARAMETERS FOR THE FIELD OF SECURITY OF ACCESS SYSTEMS - Davydenko , Anatolii; Vysotska , Olena; Prygara , Mykhailo; Bychkov, Volodymyr (Ukrainian Information Security Research Journal, 2024)
Access control systems attract attention due to the priority of contact with the information system and the criticality of failures in its operation. Therefore, it is an important typical subsystem of any information system. The developer of a new information system is always faced with the dilemma of either developing this subsystem from scratch or adapting a ready-made solution. As far as the cost and copyright aspects are excluded, the technical feasibility and complexity of such adaptation is critical to resolving the dilemma. This article explores the potential application of a typical access differentiation subsystem in various subject areas, with an emphasis on the uniqueness of the scope and the definition of the requirements and constraints that arise during the adaptation procedure. It was intuitively understood that the proximity of the subject areas of information systems affects the effectiveness of adaptation, but for a preliminary assessment of the feasibility of its use, a methodology is needed that allows obtaining a qualitative or quantitative result. A possible approach is semantic analysis and expendation based on various mathematical methods, including fuzzy ones. The aim of the article is to study the possibilities and prospects of using the technology of adaptation of access differentiation systems in the expansion of the subject area. The methods make it possible to create more flexible means of evaluation based on semantic analysis. The use of methods allows you to obtain results, both in quantitative and qualitative form.